Placental volume at 11 weeks is associated with offspring bone mass at birth and in later childhood: Findings from the Southampton Women's Survey. (15th September 2020) - Woolford, S.J.; Curtis, E.M.; D'Angelo, S.; Mahon, P.; Cooke, L.; Cleal, J.K.; Crozier, S.R.; Godfrey, K.M.; Inskip, H.M.; Cooper, C.; Harvey, N.C.
Abstract: Objectives: To investigate associations between placental volume (PV) at 11 weeks' gestation and offspring bone outcomes at birth, 6 years and 8 years. Methods: 3D ultrasound scanning was used to assess 11 week PV in a subset (n = 236) of the Southampton Women's Survey (a prospective mother-offspring cohort). Maternal anthropometric measures and lifestyle information were obtained pre-pregnancy and at 11 weeks' gestation. Offspring dual-energy x-ray absorptiometry scanning was performed within 2 weeks postnatally and at 6 and 8 years. Linear regression was used to assess associations between PV and bone outcomes, adjusting for offspring age at DXA and sex, and maternal age, height, smoking status, walking speed and triceps skinfold thickness. β are SD change in bone outcome per SD change in PV. Results: In adjusted models, 11 week PV was positively associated with bone area (BA) at all time points, with evidence of persisting associations with increasing childhood age (birth: n = 80, β = 0.23 [95%CI = 0.03, 0.42], 6 years: n = 110, β = 0.17 [-0.01, 0.36], 8 years: n = 85, β = 0.13 [-0.09, 0.36]). Similar associations between 11 week PV and bone mineral content (BMC) were observed. Associations with size-corrected bone mineral content were weaker at birth but strengthened in later childhood (birth: n = 78, β = 0.07 [-0.21, 0.35], 6 years: n = 107, β = 0.13 [-0.08, 0.34], 8 years: n = 71, β = 0.19 [-0.05, 0.43]). Conclusions: 11 week PV is associated with DXA bone measures at birth, with evidence of persisting associations into later childhood. Further work is required to elucidate the contributions of placental morphology and function to gestational influences on skeletal development. Highlights: Placental volume measured at 11 weeks' gestation is associated with neonatal bone area and bone mineral content. There was evidence of persisting associations between placental size and offspring bone measures in later childhood. Offspring bone health has now been associated with placental volume in early pregnancy, as well as mid-pregnancy and birth.